Pendampingan Ekonomi Kreatif Untuk Menunjang Kesejahteraan Masyarakat Desa Tambak Lekok Pasuruan - Muhammad Bashori; Ely Masnawati (Universitas Darunnajah, Jakarta, Indonesia, 2024)
Creative Economy is one of the main drivers for improving community welfare, especially in rural areas. Because with the creative economy will make more productivity and empowerment for the community. This article describes the implementation of the mentoring program in the Tambak Lekok village area as an effort and endeavor to empower and improve community welfare. Mentoring is carried out through the development of skills, innovation, products based on local potential, and digital marketing as well as assistance related to business management. The results of this mentoring program can provide and show an increase in community income, business diversification and strengthening community capacity in facing economic challenges by utilizing digitalism.